Translation of the Names of Chinese Calligraphy from Skopos Theory - Zhang, Guangqi (Advances in Social Sciences Research Journal, 2014)
Chinese calligraphy is an ancient and historic art. Ranging from seal script, clerical script, regular script, running script, to cursive script, the calligraphy has been sending out the charm of art. Chinese calligraphy is not only a carrier of the Chinese cultural heritage, but also the media to show the history of the Chinese nation of thousands of years. Therefore, Chinese calligraphy is a brilliant art of Chinese culture, and one of the world’s unique treasures. Based on Skopos theory, this paper explores the effective translation methods of the names of Chinese calligraphy, and explains Chinese cultural values and the inside meanings.